Malay cultural responsive landscape: inspiration for design emotion in modern landscape architecture - Ismail, Nor Atiah; Nangkula, Utaberta; Ismail, Sumarni; Mohd Yunus, Mohd Yazid (American-Eurasian Network for Scientific Information, 2015)
Scholars determines that man cannot exist independently and must cherish the relationship binding him with the rest. This relationship is expressed usually by the landscape in which we live. This statement supports the landscape evolution which has started during the Romanticism Movement. This movement is fundamentally the awakening point in environmental consciousness. It was developed during the eighteenth century through the nineteenth century where at that time, researchers have established provision of new scientific ideas that made possible a new perspective in rational comprehension, as opposed to the spontaneous enjoyment of the landscape. From this moment, people start to recognize that there was a variety of landscape characters that determined its categories. One of it is known as cultural landscape. Cultural landscape however, being generously replaced by modernism and heterogeneous characteristics. This paper discusses the importance of the Malay cultural landscape in bringing people close to their living environment and feeling the sense of belonging towards their outdoor spaces. Information elaborated in this paper is an inspiration for current landscape architects who seem to focus more on design form and elements; rather than functional spatial design and space emotion.